Comparing welfare regime changes: living standards and the unequal life chances of different birth cohorts - Chauvel, Louis (Luxembourg, 2008)
"The cohort sustainability of welfare regimes is of central importance to most long-term analyses of welfare state reforms (see for example: Esping-Andersen et al., 2002). A complement to these analyses shows that changes in intra versus inter cohort inequalities are major outcomes or consequences of the trajectories of the different welfare regimes. Previous comparative research papers show the difference between France and the United-States, since the American intra-cohort inequalities have increased strongly for the last three decades, when the French case show less intra-cohort inequalities and more inter-cohort imbalances at the expense of younger generations of adults (Chauvel 2006). Here, we propose a comparison between the US, Danish, French, and Italian dynamics of distribution of after tax and transfers equivalised income by age, period and cohort, to assess how different welfare regimes gave different trade-offs between intra and inter cohort inequality. The Luxembourg Income Study (LIS) data are used to analyze the transformations of the intra cohort inequalities (based on interdecile ratios) and the changes in the cohort life chances. The main result is that the conservative and the familialistic welfare regimes are marked by more inter-cohort inequalities to the expense of young social generations, who are relatively impoverished, when the social-democrat and the liberal ones show less inter-cohort redistribution of resources, but increasing intra-cohort inequality, particularly in the case of the US. In terms of cohort sustainability of welfare regimes, the French and Italian dynamics seem to be unsustainable since the contemporary well-off seniors are flowed by impoverished mid-aged groups who will be poor seniors of the 2020's."